13C MRS Studies of the Control of Hepatic Glycogen Metabolism at High Magnetic Fields - Miller, Corin O.; Cao, Jin; Zhu, He; Chen, Li M.; Wilson, George; Kennan, Richard; Gore, John C. (Frontiers in Physics, 2017)
Introduction: Glycogen is the primary intracellular storage form of carbohydrates. In contrast to most tissues where stored glycogen can only supply the local tissue with energy, hepatic glycogen is mobilized and released into the blood to maintain appropriate circulating glucose levels, and is delivered to other tissues as glucose in response to energetic demands. Insulin and glucagon, two current targets of high interest in the pharmaceutical industry, are well known glucose-regulating hormones whose primary effect in liver is to modulate glycogen synthesis and breakdown. The purpose of these studies was to develop methods to measure glycogen metabolism in real time non-invasively both in isolated mouse livers, and in non-human primates (NHPs) using 13C MRS. Methods: Livers were harvested from C57/Bl6 mice and perfused with [1-13C] Glucose. To demonstrate the ability to measure acute changes in glycogen metabolism ex-vivo, fructose, glucagon, and insulin were administered to the liver ex-vivo. The C1 resonance of glycogen was measured in real time with 13C MRS using an 11.7T (500 MHz) NMR spectrometer. To demonstrate the translatability of this approach, NHPs (male rhesus monkeys) were studied in a 7 T Philips MRI using a partial volume 1H/13C imaging coil. NPHs were subjected to a variable IV infusion of [1-13C] glucose (to maintain blood glucose at 3-4x basal), along with a constant 1 mg/kg/min infusion of fructose. The C1 resonance of glycogen was again measured in real time with 13C MRS. To demonstrate the ability to measure changes in glycogen metabolism in vivo, animals received a glucagon infusion (1 μg/kg bolus followed by 40 ng/kg/min constant infusion) half way through the study on the second study session. Results: In both perfused mouse livers and in NHPs, hepatic 13C-glycogen synthesis (i.e. monotonic increases in the 13C-glycogen NMR signal) was readily detected. In both paradigms, addition of glucagon resulted in cessation of glycogen synthesis and induction of glycogen breakdown. In the perfused liver, inclusion of insulin was able to dose-dependently block the effect of glucagon. Conclusion: Hepatic glycogen synthesis, as well as acute hormonally-induced changes thereof, can be measured using 13C MRS at high magnetic fields both ex-vivo